Political Hate Speech and the Identity Factor in the European Space - Katica Kulavkova (European Scientific Journal, ESJ, 2026)
Utilizing normative frameworks of the United Nations, the Council of Europe, and the European Union, this article introduces the term ‘political hate speech’ to describe identity-denying discourse produced, legitimized, or tolerated by state institutions and supranational bodies. Drawing on Jeremy Waldron’s theories of dignity and civic assurance (2012), the study conceptualizes hate speech as political, linguistic, and symbolic violence that undermines the publicly guaranteed status of individuals and groups as equal bearers of rights.Rather than treating hate speech primarily as a subjective offense, the analysis foregrounds its structural harms, showing how it erodes the social conditions and identity markers essential for democratic inclusion, mutual recognition, and reciprocity. Identity-based political propaganda destabilizes civic guarantees of ethnic, national, religious, cultural, historical, and linguistic recognition by generating both symbolic and legal forms of exclusion and discrimination.Rather than treating hate speech primarily as a subjective offense, this analysis foregrounds its structural harm, revealing how it corrodes the social conditions and identity markers essential for democratic inclusion, mutual recognition, and reciprocity. Identity-based political propaganda destabilizes civic guarantees of ethnic, national, religious, cultural, historical, and linguistic recognition by producing both symbolic and legal forms of exclusion and discrimination.The Macedonian case serves as a focal study of internationalized political and media hate speech, illustrating legal, social, and psychological consequences such as collective anxiety, stigmatization, defamation, and trauma. Comparative references—including Catalonia, the Baltic and Balkan states, Roma communities, and aspects of social rights affecting British immigrants—highlight broader patterns of identity-based political action across Europe and underscore differences between EU member states and some nonmember states. These examples expose significant normative and institutional challenges for European governance in safeguarding dignity, equality, and civic inclusion amid growing pluralism.The absence of universal consensus and variation in definitions and regulatory approaches to political hate speech—when balanced against freedom of expression, democratic principles, and individual and collective rights—generates latent and explicit interethnic, intergovernmental, and media tensions. The prevailing tolerance of discourses that discriminate on identity grounds should be replaced by a more humane, nonviolent paradigm and narrative.